2017
DOI: 10.1021/acsami.7b08066
|View full text |Cite
|
Sign up to set email alerts
|

Surface/Interface Carrier-Transport Modulation for Constructing Photon-Alternative Ultraviolet Detectors Based on Self-Bending-Assembled ZnO Nanowires

Abstract: Surface/interface charge-carrier generation, diffusion, and recombination/transport modulation are especially important in the construction of photodetectors with high efficiency in the field of nanoscience. In the paper, a kind of ultraviolet (UV) detector is designed based on ZnO nanostructures considering photon-trapping, surface plasmonic resonance (SPR), piezophototronic effects, interface carrier-trapping/transport control, and collection. Through carefully optimized surface/interface carrier-transport m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Zinc oxide nanowires (ZnO NWs) are now well-established candidates for (opto)electronic integration in diverse applications such as chemical 1 and biological sensors, 2,3 photodetectors, 4,5 nanogenerators, 6 and piezotronic devices. 2,7 Along with other compound semiconductor materials such as GaN, GaAs, and InP, single crystal ZnO NWs of high crystalline quality, large aspect ratio, and small diameter can be achieved using high-temperature CVD "bottom-up" growth methods.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Zinc oxide nanowires (ZnO NWs) are now well-established candidates for (opto)electronic integration in diverse applications such as chemical 1 and biological sensors, 2,3 photodetectors, 4,5 nanogenerators, 6 and piezotronic devices. 2,7 Along with other compound semiconductor materials such as GaN, GaAs, and InP, single crystal ZnO NWs of high crystalline quality, large aspect ratio, and small diameter can be achieved using high-temperature CVD "bottom-up" growth methods.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The performance of PD devices can be improved by the following ways: (a) enhancing the interaction between light and matter; (b) decreasing the adverse effects of defects; and (c) adjustment of electronic characteristics [60]. Therefore, various approaches, such as doping [61], surface functionalization [56,[62][63][64][65][66][67][68], surface carrier transport modulation [34], interface carrier-trapping/transport control [46], piezo-phototronic effects [69][70][71][72][73][74], and so on, have been utilized to improve the photoresponse performance of low-dimension nanostructure PDs for use in practical applications. The following section lists several ways to deal with surface/interface issues for improving performance of the photodetectors.…”
Section: Surface/interface Engineering For Improvement Of Photodetectmentioning
confidence: 99%
“…It can be observed that charge carrier generation, diffusion, and recombination modulation are all very important considerations in the construction of high-efficiency PDs [46]. The sensitivity, response speed, spectral selectivity, signal-to-noise ratio, and stability of detection are much more important factors to judge the performance of PDs [34].…”
Section: Introductionmentioning
confidence: 99%
“…Various approaches have been adopted to improve the photoresponse performance of 1D ZnO nanostructure photodetectors for use in practical applications. Generally, surface and interface carrier transport modulation are the main routes used to raise photoresponsivity [130]. For instance, Lao et al [131] manipulated and functionalized the polymer polystyrene sulfate (PSS) on the surface of ZnO nanobelts using a layer-by-layer self-assembly method.…”
Section: Photodetectorsmentioning
confidence: 99%